تعليم اللغة العربية بإستراتيجية رسم الخرائط الذهنية في جامعة سنان دراجات لامونجان الإسلامية - Rohmatun Nurul Hidayah; Siti Alfi Faridlotul Jannah (Program Studi Pendidikan Bahasa Arab bekerjasama dengan Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan., 2021)
Abstract: Arabic language consists of 3 elements and 4 skills, 3 elements Sound, vocabulary and grammar. And 4 skills, listen, speak, read and write . In learning Arabic I for students of the Sunan Drajat Lamongan Islamic Boarding School University, using an interesting strategy so that students are able to learn Arabic I well. This mind mapping strategy is a mind map which is a technique of utilizing the whole brain by using visual images and other graphic infrastructure to form a deep impression. This study uses a quantitative approach with experimental research methods. The experimental research method is a research method carried out by experiment, which is a quantitative method, used to determine the effect of the independent variable on the dependent variable under controlled conditions. The experimental research design used was one group pretest posttest design, by holding a pretest first then there was treatment and ending with the posttest, thus the treatment can be known to be more accurate, because it can compare with the situation before being given the treatment. The results of this study are that ha higher than ho, by showing the t-test number 2.4 and t-table 1.67, that the t-test is greater than the t-table. So there is a relationship between learning Arabic I for the students of the Sunan Drajat Lamongan Islamic Boarding School University in the Mind Mapping strategy.